Instructional Design in Calculus Based on Realistic Mathematics Education Approach (RME) and its Effectiveness on Problem solving skills among high school students - Alssenai, Faisal Ali Saleh; Mahdi, Abullah Abbas; Al-Baqeri, Dhikra Mohammad (Journal of Curriculum and Teaching Methodology, 2023)
This research aims to investigate the effectiveness of instructional design in calculus based on realistic mathematic education approach (RME) to develop problem solving skills among secondary school students. To achieve this, the researcher built an instructional design in the unit of limits, continuous and derivatives for 2nd grade of secondary school based on realistic mathematic education.The research sample consisted of 122 female students from the 2nd year of scientific secondary school in Somiah School for Girls in the Al-Sabeen District in the capital Sana’a, were chosen intentionally and divided into two groups, an experimental group(b) (61 students) was taught through instructional design and a control group(c)(61 students) was taught through normal curriculum. The data was collected by test problem solving skills was built, and applied to both groups after verifying its validity and reliability. The results indicated statistical significance deference (α =0.05) among the arithmetical mean for both groups, in favor of experimental group, in addition to the teaching design’s effectiveness in developing problem solving skills. According to the results of the research, the researchers recommended to be taken advantage from RME approach for development of mathematics curricula, as well as development teacher’s performance by developing preparation programs and training during service.